Microwave hydrothermal synthesis and Characterization of copper sulfide with different morphologies - Anukorn Phuruangrat (2018)
CuS products with different morphologies (flower-like, nanoparticles and nanoplates) have been synthesized by microwave-hydrothermal method using different sources of copper (Cu(CH 3 COO) 2 ·H 2 O, CuBr and CuCl 2 ·2H 2 O) and sulfur (CH 3 CSNH 2 and NH 2 CSNH 2 ). The as-synthesized CuS products were analyzed by XRD, SAED and Raman spectroscopy. XRD patterns of the products can be indexed to hexagonal CuS phase as compared to JCPDS database no. 78-0876. Raman spectra show a sharp peak of CuS at 470 cm -1 , assigned to the S-S stretching mode of S 2 ions at 4e sites. In addition, their morphologies were investigated by SEM and TEM. They were found that the products shaped like microflowers, nanoparticles and nanoplates controlled by the starting materials.